2006
DOI: 10.1186/1471-2202-7-25
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of ketamine and toxic interactions with psychostimulants

Abstract: Background: The anesthetic drug ketamine (KT) has been reported to be an abused drug and fatal cases have been observed in polydrug users. In the present study, considering the possibility of KT-enhanced toxic effects of other drugs, and KT-induced promotion of an overdose without making the subject aware of the danger due to the attenuation of several painful subjective symptoms, the intraperitoneal (i.p.) KT-induced alterations in behaviors and toxic interactions with popular co-abused drugs, the psychostimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 51 publications
(57 reference statements)
1
16
0
Order By: Relevance
“…New psychoactive substances are available in various formulations and are mainly used as legal substitutes for traditional drugs of abuse. One of the largest and most important groups are psychostimulants, which affect a range of behavioral patterns in humans ( 1 ) and laboratory animal models ( 2 , 3 ). It has been demonstrated that the repeated administration of psychostimulants to rodents ( 2 , 4 8 ) and humans ( 9 ) can lead to addiction, induce changes in emotional states such as fear, anxiety, and depression, interfere with social behavior, and cause cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…New psychoactive substances are available in various formulations and are mainly used as legal substitutes for traditional drugs of abuse. One of the largest and most important groups are psychostimulants, which affect a range of behavioral patterns in humans ( 1 ) and laboratory animal models ( 2 , 3 ). It has been demonstrated that the repeated administration of psychostimulants to rodents ( 2 , 4 8 ) and humans ( 9 ) can lead to addiction, induce changes in emotional states such as fear, anxiety, and depression, interfere with social behavior, and cause cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, animal data regarding the impact of ketamine on anxiety behaviors are contradictory: in a study conducted by Silvestre et al, 45 ketamine was found to produce anxiogenic-like effects in rats, but in another study, the drug was shown to promote anxiolytic responses (in the elevated plus maze). 46 Similarly, the evidence for an anxiolytic-like effect of ketamine in humans is equivocal and is probably subject to complex dose-and-time effects. For instance, in a study of healthy human volunteers, the participants reported a decrease in anxiety after a low dose of ketamine (0.1 mg/kg intravenously), but an increase in anxiety at a higher dose (0.5 mg/kg intravenously).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of ketamine effects on the ETM rats performance, acutely or 24 h after its administration, reinforces the controversial findings reported in previous studies, as described in table 1. For example, anesthetic doses of ketamine induced anxiolytic-like (Hayase et al, 2006), anxiogenic-like (Morena et al, 2017) or no effect (Magalhaes et al, 2017) in different tests of anxiety. Regarding sub-anesthetic doses of ketamine, similar mix of outcomes has been previously reported (as detailed in Table 1).…”
Section: New Findingsmentioning
confidence: 99%
“…For instance, the genetic background of a strain is among the several factors that may affect the behavioral responses of the animals to a drug Võikar et al, 2001). Ketamine 30 mg/kg produced an anxiolytic-like effect on male ICR mice (Hayase et al, 2006) and no effect on male 129S6/SvEvTac mice (Brachman et al, 2016) submitted to the EPM. Ketamine 10 mg/kg induced an anxiolytic-like effect in NSF, but did not alter the behavior in the EPM and in the context and cued fear conditioning (Autry et al, 2011).…”
Section: New Findingsmentioning
confidence: 99%